Distribution and origin of nitrate in groundwater in an urban and suburban aquifer in Mar del Plata, Argentina - Martinez, Daniel Emilio (2014)
The impact of urbanization on groundwater quality is of special concern for water managers dealing with the provision of drinking water to large urban centers. Nitrate is one of the most common contaminants found in urban aquifers. This paper presents a case study aiming at evaluating the distribution and sources of nitrate in an urban aquifer in the city of Mar del Plata, Argentina. Four study zones under different land uses, including a pristine, a semi-rural, an intermediate, and an urban area, were evaluated as a part of this study. The three latter zones are linked by the groundwater flow system. The average nitrate concentration in the pristine area is 6.7 mg/L as nitrate and is over the permissible level of 50 mg/L for drinking water in the other areas. In the semi-rural area it ranges from 39.2 to 107.1 mg/L with an average value of 38.2 mg/L and the nitrate concentration tends to decrease in the intermediate zone to an average value of 38.2 mg/L; however, values above 60 mg/L are also observed there. Then the nitrate concentration in the urban area water is higher than that in the intermediate zonewater ranging from 48.2 to 100.3 mg/L with an average value of 67.3 mg/L. Data on the stable isotopes 15N and 18O in nitrate show that the main sources of nitrate in the study area are manure associated to agriculture uses and cesspools in the semi-rural area, and leakage of the sewage distribution network in the urban area, espectively. This is supported by a previous study which found that 20 % of the water flooding many underground structures in the city came from leakage of the sewage network. No evidence of nitrate attenuation by denitrification was found in the groundwater. This study has shown that aquifers in urban areas can be affected by agricultural activity in the upstream areas and leakage of the sewage network in the urban area.